2015
DOI: 10.1080/15384047.2015.1056415
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of randomized trials on the role of targeted therapy in the management of advanced gastric cancer: Evidence does not translate?

Abstract: It is still uncertain if targeted therapy-based regimens in advanced gastric cancer actually produce survival benefit. To shed light on this important question, we performed a systematic review and meta-analyses on each relevant targeted-pathway. By searching literature databases and proceedings of major cancer meetings in the time-frame 2005-2014, 22 randomized clinical trials exploring targeted therapy for a total of 7022 advanced gastric cancer patients were selected and included in the final analysis. Bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 109 publications
0
28
0
Order By: Relevance
“…The efficacy of targeted therapy was evaluated in three meta-analyses [10, 18, 22]. As for OS, one of them favored targeted therapy of antiangiogenic and HER2 pathway but not for EGFR pathway compared with conventional chemotherapy [10].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The efficacy of targeted therapy was evaluated in three meta-analyses [10, 18, 22]. As for OS, one of them favored targeted therapy of antiangiogenic and HER2 pathway but not for EGFR pathway compared with conventional chemotherapy [10].…”
Section: Resultsmentioning
confidence: 99%
“…As for OS, one of them favored targeted therapy of antiangiogenic and HER2 pathway but not for EGFR pathway compared with conventional chemotherapy [10]. One showed that in patients with Eastern Cooperative Oncology Group Performance Status (ECOG-PS) of 0, targeted therapy did not report a significant benefit over BSC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations